New results in numerical and experimental fluid mechanics X : contributions to the 19th STAB/DGLR Symposium, Munich, Germany 2014 /: contributions to the 19th STAB/DGLR Symposium, Munich, Germany 2014. ([2016]) - Unknown
No abstract available